CEO environmental experience and firms’ environmental disclosure - Isidro, H.; Santos, J. V. J. (EAA Annual Congress, 2025)
Using a novel measure of managerial skill based on CEOs’ functional expertise, we find that our CEO skills measure is positively associated with both the likelihood and quality of non-GAAP disclosures. Firms led by highly skilled CEOs are more likely to follow the European Securities and Markets Authority (ESMA) guidelines for transparent non-GAAP reporting. Specifically, CEOs with broader skill sets tend to exclude items from GAAP earnings more consistently over time when calculating their non-GAAP numbers, report non-GAAP information even when the GAAP earnings surprise is small, provide numerical reconciliations between GAAP and non-GAAP earnings, give higher emphasis to GAAP earnings, use non-GAAP earnings less to meet or beat analysts’ forecasts, and exclude fewer recurring items in their non-GAAP calculations. Among 20 managerial skills, expertise in accounting and finance, corporate governance, and company experience are the skills most strongly linked to transparent non-GAAP disclosure practices. These results are robust across several strategies to mitigate endogeneity, including instrumental variable approaches, CEO turnover analysis, a macroeconomic event, and controlling for managerial ability. Our results highlight the importance of individual managerial skills in influencing voluntary disclosure.